Nlrc3 Knockout Mice Showed Renal Pathological Changes After HTNV Infection - Ma, Ruixue; Zhang, Xiaoxiao; Shu, Jiayi; Liu, Ziyu; Sun, Wenjie; Hou, Shiyuan; Lv, Yunhua; Ying, Qikang; Wang, Fang; Jin, Xia; Liu, Rongrong; Wu, Xingan (Frontiers in Immunology, 2021)
Hantaan virus (HTNV) infects humans and causes hemorrhagic fever with renal syndrome (HFRS). The development of well-characterized animal models of HFRS could accelerate the testing of vaccine candidates and therapeutic agents and provide a useful tool for studying the pathogenesis of HFRS. Because NLRC3 has multiple immunoregulatory roles, we investigated the susceptibility of Nlrc3−/− mice to HTNV infection in order to establish a new model of HFRS. Nlrc3−/− mice developed weight loss, renal hemorrhage, and tubule dilation after HTNV infection, recapitulating many clinical symptoms of human HFRS. Moreover, infected Nlrc3−/− mice showed higher viral loads in serum, spleen, and kidney than wild type C57BL/6 (WT) mice, and some of them manifested more hematological disorders and significant pathological changes within multiple organs than WT mice. Our results identify that HTNV infected Nlrc3−/− mice can develop clinical symptoms and pathological changes resembling patients with HFRS, suggesting a new model for studying the pathogenesis and testing of candidate vaccines and therapeutics.